Fotografia maranhense: estudo de caso da série Na trilha do cangaço o sertão que Lampião pisou, de Márcio Vasconcelos. - SOARES, Maria Thereza Gomes de Figueiredo (2018)
The purpose of this study is to observe the photography making in São Luís in the present. Photography, in its digital era, grows in volume of imagery, with an ease of making images at a lower cost, as well as with instantaneity and easy dissemination. The shortage of research in the history of São Luís photography is an obvious fact. The intention of this work is to research the contemporary photographic modes of production using a cut on the series of literary work of the Maranhão - born author Márcio Vasconcelos Na trilha do Cangaço o sertão que Lampião pisou. This work was selected because of its expressive character and the availability of the author to cede process documents, allowing analysis through the creation networks metodology, which deals with the pondering of the artistic work through the creation documents. Hereafter, the method of formal analysis proposed by the author Donis A. Dondis was used, from the publication Sintaxe da Linguagem Visual. To complement this step, the triangulation method was used: image analysis, data collection and theoretical reference. Thus, the images that will be analyzed are short cuts of the publication aforementioned, which will be approached the way the artist interprets the proposed historical theme, its plastic choices and the senses of the images. To do so, data from the historiography of photography in São Luís and then the photography of Márcio Vasconcelos will be listed, through interviews, data collection and interpretation, supported by the theoretical framework.